Problematika Hukum Bangunan di atas Tanah Berstatus Izin Pemakaian Tanah (IPT) atau Surat Ijo sebagai Objek Jaminan - Suhaila Ritonga; Muhammad Yamin lubis; Rosnidar Sembiring (CV Rewang Rencang, 2025)
The legal issues surrounding buildings on land with Land Use Permit (IPT) or Green Certificate status as fiduciary collateral objects pose serious problems in Indonesia's land law system. IPT, issued by local governments, has weak legal standing due to its temporary nature and revocable status, while buildings constructed on such land are often used as fiduciary collateral. This creates significant legal uncertainty for both creditors and debtors, particularly during collateral execution in cases of default. The research employs normative juridical methods through literature study to analyze primary, secondary, and tertiary legal materials. The study concludes that IPT faces juridical constraints as it is not classified as land rights under the Basic Agrarian Law, resulting in extremely low legal certainty for fiduciary collateral arrangements.